Bovine colostral cells—the often forgotten component of colostrum - Gonzalez, Diego; Dus Santos, Maria Jose (American Veterinary Medical Association, 2018)
At birth, neonatal calves have all the essential immune components they need as adult cattle; however, it takes at least 2 to 4 weeks for those components to become fully functional.1,2 The immune system does not become completely mature until the animal is 5 to 8 months old; for example, it takes 8 months for T cells (CD4+, CD8+, and T-cell receptor gδ+ cells) to reach peak numbers.3 Thus, the immature immune system of young calves likely moderates rather than prevents disease. This does not imply that young (< 8 months old) calves cannot respond to antigens; it simply means that the response to those antigens is weaker, slower, and easier to overcome than it will be when the immune system is mature.4